Implementing participatory approaches in formulating regional forest policy. (4th March 2005) - Ananda, Jayanath
Forest policy-makers increasingly recognise the importance of public participation in planning and policy-making endeavours. In many countries, public participation has been institutionalised into national forest policy. Despite the stated policy assurances, implementing participatory approaches has been a challenging task. This paper examines the public involvement in forest policy-making, particularly focusing on the Regional Forest Agreement (RFA) programme in Australia. The RFA is regarded as the most ambitious, expensive and comprehensive resource planning exercise ever undertaken in the country. The evidence suggestes that various participatory and deliberative approaches have been used under the RFA to allow for a plurality of environmental values, but that the integration of public values into final decision-making has been unsatisfactory. Process design, commitment and inadequate attention paid to conflict resolution can be attributed as reasons for sub-optimal outcomes.